Streptolysin O II. Relationship of Sulfyhdryl Groups to Activity - Van Epps, Dennis E. (1971)
Streptolysin O (SO), a group A streptococcal toxin, exists in two forms, a reduced active state and an oxidized reversibly inactive state. Activity is measured by red blood cell hemolysis. SO is a labile toxin, and, with time, activity is irreversibly lost. The rate of activity loss is slowed by incubation with 0.1 m 2-mercaptoethanol or 0.01 m ethylenediaminetetraacetic acid (EDTA). The effect of EDTA can be reversed by excess MgSO(4). Reversibly oxidized SO is activated by cleavage of disulfide bonds. When the free sulfhydryl groups of the active SO are alkylated with iodoacetamide, complete and irreversible loss of activity results. Periodate (0.01 m) oxidation also causes complete loss of activity which may be due to oxidation of sulfhydryl groups. SO in the active form reacts with Fe(2+), Cu(2+), Ca(2+), and Mg(2+), causing loss of activity in various degrees depending on the ions and the concentration used. Ferric and cupric ions are most effective and cause loss of activity at concentrations on the order of 10(−4)m. The reversibly oxidized form of SO is not influenced by exposure to cupric ions (0.01 m), indicating that the reaction is only with the active form of SO, probably involving the free sulfhydryl groups. These groups may be responsible for the direct binding of the toxin to the target membrane or for the maintenance of the proper conformation for activity.